Effect of radical prostatectomy on levels of cancer related epitopes in circulating macrophages of patients with clinically localized prostate cancer. Issue 12 (20th July 2017) - Todenhöfer, Tilman; Hennenlotter, Jörg; Keller, Gabriel; Neumann, Tim; Stenzl, Arnulf; Bedke, Jens
Abstract : Objective: Epitopes of the apoptosis related protein DNaseX (Apo10) and the pentose‐phosphate‐pathway associated protein transketolase‐like 1 (TKTL1) have been shown to be increased in circulating macrophages of patients with different cancer types including prostate cancer (PC). So far, the effect of cancer‐specific therapies on the levels of these markers in blood samples of patients with PC has not been evaluated yet. The aim of the present study was to prospectively assess the effect of surgical removal of the prostate on levels of Apo10 and TKTL1 in blood macrophages using Epitope Detection In Monocytes (EDIM). Methods: We prospectively enrolled 174 patients with clinically localized PC undergoing radical prostatectomy. Peripheral blood was collected preoperatively in all patients and postoperatively in a subgroup of 72 patients. We separately assessed the proportion of CD14/CD16‐positive monocytes expressing Apo10 and TKTL1 using flow cytometry. The proportion of positive cells was multiplied by ten to generate a score for Apo10 and TKTL1, separately. Pre‐ and postoperative scores of Apo10 and TKTL1 were compared. Moreover, results were correlated with clinicopathologic parameters. Results: In the total cohort, Median preoperative Apo10 and TKTL1 scores were 136 (Range 101‐254) and 139 (102‐216). In patients who underwent blood collection and testing either pre‐ and postoperatively ( n = 72), median pre‐ versus postoperative scores were 132 (101‐215) versus 103 (70‐156) for Apo10 ( P < 0.0001) and 140 (102‐212) versus 115 (84‐187) ( P < 0.0001) for TKTL1. Following radical prostatectomy, 56 (77.7%) and 59 (81.9%) patients in the cohort of patients with blood collection before and after prostatectomy showed a decrease of Apo10 and TKTL1 expressing monocytes. TKTL1 and Apo10 did not show any correlation with known histopathologic and clinical risk parameters. Conclusions: The present study demonstrates that surgical removal of the primary tumor leads to a significant decrease of Apo10 and TKTL1 expressing macrophages. This observation further encourages studies assessing the optimal clinical utility of EDIM‐based detection of Apo10 and TKTL1 in patients with PC.